2006
DOI: 10.1001/archpsyc.63.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Implication of SSAT by Gene Expression and Genetic Variation in Suicide and Major Depression

Abstract: These data suggest a role for SSAT, the rate-limiting enzyme in the catabolism of polyamines, in suicide and depression and a role for the SSAT342 locus in the regulation of SSAT gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
146
5
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 164 publications
(169 citation statements)
references
References 31 publications
16
146
5
2
Order By: Relevance
“…[21][22][23] Two genes involved in the catabolism of polyamines (SAT and SMOX), significant in several regions, suggest the possible association of suicide and depression with defects in the polyamine stress response system. Reduced expression of SAT in depressed and nondepressed suicide groups was previously shown in motor cortex, superior frontal gyrus and orbital gyrus, 9 with correspondingly reduced levels of SAT protein. A number of genes functioning in polyamine metabolism have also been implicated in schizophrenia through microarray analysis.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…[21][22][23] Two genes involved in the catabolism of polyamines (SAT and SMOX), significant in several regions, suggest the possible association of suicide and depression with defects in the polyamine stress response system. Reduced expression of SAT in depressed and nondepressed suicide groups was previously shown in motor cortex, superior frontal gyrus and orbital gyrus, 9 with correspondingly reduced levels of SAT protein. A number of genes functioning in polyamine metabolism have also been implicated in schizophrenia through microarray analysis.…”
Section: Discussionsupporting
confidence: 53%
“…In comparison with microarray studies of schizophrenia and bipolar disorder, only a handful of studies have been reported on gene expression changes associated with major depression and completed suicide. [8][9][10] There is a clear need for further investigation of the gene expression changes associated with these phenotypes to gain better insight into their possible biological mechanisms. 11 We have carried out a microarray-based investigation of these brain regions in both depressed and nondepressed suicide victims in comparison with controls, to identify novel candidate systems and biological pathways that may be involved in suicide and major depression.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of the ANOVA and subsequent t-tests is commonly referred to as Fisher protected least significant difference (LSD) test. In the case of gene expression studies of complex traits such as psychiatric disorders, it has been suggested to use less stringent criteria in the initial analysis stages, 76 and the use of only t-tests or Fisher protected LSD test has been commonly accepted in psychiatric brain expression studies 50,64,65 as well as in other research areas. 77 Multiplicity is always a concern when performing microarray analysis and many correction procedures have been developed to address it such as the Bonferroni-method or false discovery rate-based methods.…”
Section: Discussionmentioning
confidence: 99%
“…More overlap was seen for instance in a previous study by our group exploring expression in cortical regions. 50 Some overlap was also observed between the SMD-S and S-C comparisons, suggesting that these genes are likely to be involved in suicide-related processes independently of underlying depressive psychopathology. In the amygdala, for instance four genes were observed in common for those comparisons (MAX, MYEF2, YWHAB and GRIPAP1) whereas only one was observed in BA24 (CIRBP) and three in BA29 (RGN, TDE1 and CKLFSF1).…”
Section: Nomentioning
confidence: 97%
“…This pathway includes 3 rate-limiting enzymes, one of which is Sadenosylmethionine decarboxylase (AMD1). The initial support for the involvement of the polyamine system in suicide came from observations that spermidine/spermine N 1 -acetyltransferase (SAT1) gene expression was downregulated in numerous brain regions in suicide completers as compared to control subjects (Guipponi et al, 2009;Sequeira et al, 2006). Moreover, functionally characterized genetic variants in the promoter region of SAT1 were associated with suicide (Fiori, Mechawar, & Turecki, 2009;Sequeira et al, 2006).…”
Section: Introductionmentioning
confidence: 99%